2016
DOI: 10.1016/j.jaac.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events During Pregnancy and Offspring Depression: Evidence From a Prospective Cohort Study

Abstract: These results provide support for the fetal programming hypothesis, demonstrating that prenatal exposure to acute stress is associated with offspring depression in adolescence. Stress management may be of benefit for expectant mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 46 publications
3
50
1
Order By: Relevance
“…Although a variety of studies have found that maternal stress during pregnancy is associated with adverse offspring outcomes similar to those found in depressed populations (Betts et al, 2015; Betts et al, 2014; Brown et al, 2000; Buss et al, 2011; Da Costa et al, 1998; Kingsbury et al, 2016; Pritchard and Teo, 1994; Shah et al, 2011; Watson et al, 1999), the present study did not find any independent associations between reported maternal stress during pregnancy and risk for offspring depression. Rather, the present study only found that maternal stress during pregnancy moderated the relation between infection during pregnancy and risk for offspring depression.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Although a variety of studies have found that maternal stress during pregnancy is associated with adverse offspring outcomes similar to those found in depressed populations (Betts et al, 2015; Betts et al, 2014; Brown et al, 2000; Buss et al, 2011; Da Costa et al, 1998; Kingsbury et al, 2016; Pritchard and Teo, 1994; Shah et al, 2011; Watson et al, 1999), the present study did not find any independent associations between reported maternal stress during pregnancy and risk for offspring depression. Rather, the present study only found that maternal stress during pregnancy moderated the relation between infection during pregnancy and risk for offspring depression.…”
Section: Discussioncontrasting
confidence: 84%
“…However, another study that prospectively followed mothers and their children for a period of more than 20 years, found that high levels of maternal depression, anxiety, and stress symptoms (assessed via a 4-item, self-report inventory) during pregnancy were associated with offspring internalizing behavior problems in adolescence (Betts et al, 2014) and adulthood (Betts et al, 2015). These results were consistent with findings from another prospective population-based cohort that demonstrated an association between maternal exposure to stressful life events during early pregnancy and an increased risk for depression and elevated depressive symptoms in 17 to 18-year-old offspring (Kingsbury et al, 2016). …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prenatal depression was associated with increased odds of depression at age 12 regardless of child sex [37•]. In a second analysis from ALSPAC ( N  = 9166), maternal PNLEs were positively associated with offspring depressive symptoms and diagnosis at age 17–18, with no evidence of sex dependence [22•]. Using data from the Western Australian Pregnancy Cohort ( N  = 1214), Herbison et al found that prenatal stress was positively associated with depression/anxiety symptoms at age 20 in male but not female offspring after adjusting for postnatal childhood stress trajectories [55].…”
Section: Resultsmentioning
confidence: 99%
“…I felt heartbroken because I really wanted this child. (ROSA,14)  Reactions of the child´s father in front of the pregnancy of the adolescent It was found that the partner's reactions to the adolescent's pregnancy ranged from immediate acceptance to the imposition of abortion. However, most of the adolescents in this study received support from the child's parent, even in cases where the love relationship was over, as illustrated below:…”
Section:  Family Reactions To Teenage Pregnancymentioning
confidence: 99%